FAO's Agricultural Marketing website - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
FAO´s Agricultural Marketing website offers links to information on marketing systems for farm produce and inputs. Emphasis is on the promotion of marketing by the private sector and on the role of governments in developing an appropriate environmen